(untitled) (Tribhuvan University Journal of Microbiology, 2021)
Objectives: To determine the prevalence of Gram-negative bacteria in lower respiratory tract infections and study the biofilm producing Pseudomonas aeruginosa. Methods: This study was conducted at B & B Hospital Pvt. Ltd., Lalitpur, Nepal from February to September 2018. The samples were collected from the patients (n=420) with signs and symptoms suggestive of LRTIs. The isolated organisms were identified and antimicrobial sensitivity was performed. Among all the isolates, P. aeruginosa isolates were subjected for biofilm detection by microtitre plate method. Results: Out of 420 specimens, 90 (21.6%) were culture positive. Klebsiella pneumoniae (42.9%) was found to be the predominant organism with higher rate of resistance to antibiotics. A total of 25 isolates of P. aeruginosa were isolated among which 15 (60%) were biofilm producers. Biofilm-producing isolates of P. aeruginosa were found more resistant to the tested antibiotics. Conclusion: Gram-negative bacteria were found to be the predominant etiological agents in causing the LRTIs; K. pneumoniae, being the most commonly isolated bacteria. Most P. aeruginosa were capable of producing the biofilm. The biofilm producers were more resistant to the antibiotics. The biofilm may help increase the resistivity nature of the bacteria.